ESTIMATION THE IMPORT-ANT RELATIONSHIP BETWEEN THE BIOLOGICAL ACTIVITY AND THE STEREOCHEMICALSTRUCTURE OF THE PREPARING COMPOUNDS - and Al-saedi W. M. E; A. H; daraji (Basrah Journal of Veterinary Research)
It can be prepared a good drug or antibiotic depending on this research .its same as build a beautiful house depending on a good building factors, this research is about the important relation between the biological activity (the activity against the microbes) and stereochemical structure of the preparing compounds .To obtain this relation two ‘compounds has been prepared and tested on different species - r j (§_t.aureus, _F:._c_oﬁ, candida albicans), one of these two compounds has show more activity than the other even the difference between them is simple, this question was push us to study the more active compound (compound (l)), why it more active against the microbes, _ also this question led us to estimate the important relation ﬁve factors effecting the relation, th1s relation was obtained not from the two compounds only, but depending on more than these compounds the relation was obtained, also preparing compounds in this research are enough to illustrate the five factors leading to the important relation. _ ‘To understanding the research idea or the important relation, compound (3) was _ prepared which its more active than the two compounds. , ' All the three compounds have identify by melting point, solubility test, CHNSO analyzer, l.R., and uv-visible spectra